Advances in nanofibre research. Volume 3 - Haghi, A. K. (Smithers Rapra, 2012)
In the first two volumes of this series, we have shown that submicron-sized and nanofibres can be prepared from a polymer solution by means of electrospinning. The third volume of 'Advances in Nanofibre Research' describes the many directions in which the science and technology of polymer nanofibres is now evolving and highlights the current understanding of polymer nanofibres and nanocomposites. In this volume, readers can find chapters which compare the occurrence, stability, and functional properties of fibrous nanomaterials of different sizes and shapes. The new and emerging applications o.
Keywords: Nanofibers.; elektronické knihy; electronic books